Արտեմի Այվազյանի հուշագրությունը - Աննա Հայրապետյան (ՀՀ ԳԱԱ հրատ.)
Данная статья посвящена рукописным мемуарам композитора, дирижера, виолончелиста, народного артиста Армении, основателя армянской эстрадной музыки Артемия Айвазяна (1902-1975). Мемуары композитора дополняют представления о гражданине-музыканте, искусствоведе Айвазяне, более правдиво отражают его жизненную позицию, круг музыкальных интересов, художественные принципы и интересы, черты характера, а также обобщают творческий путь композитора. This article dedicated to unpublished memoirs of Artemi Ayvazyan (1902-1975) who was a composer, conductor, cellist, People's Artist of the ASSR, the founder of Armenian national estrada music. The memoirs take the central place in the composer’s literary inheritance. The composer’s unpublished memories enrich our knowledge about the musician-citizen and art historian, more truthfully representing A. Ayvazyan’s life position, the range of his interests in music, artistic principles and ideas, his character traits, as well as summarize the composer’s creative life.
Keywords: Music; Language and Literature